Localized Heat Therapy Improves Mitochondrial Respiratory Capacity but Not Fatty Acid Oxidation - Marchant, Erik D.; Kaluhiokalani, Jamie P.; Wallace, Taysom E.; Ahmadi, Mohadeseh; Dorff, Abigail; Linde, Jessica J.; Leach, Olivia K.; Hyldahl, Robert D.; Gifford, Jayson R.; Hancock, Chad R. (International journal of molecular sciences, 2022)
AIM: Mild heat stress can improve mitochondrial respiratory capacity in skeletal muscle. However, long-term heat interventions are scarce, and the effects of heat therapy need to be understood in the context of the adaptations which follow the more complex combination of stimuli from exercise training. The purpose of this work was to compare the effects of 6 weeks of localized heat therapy on human skeletal muscle mitochondria to single-leg interval training. METHODS: Thirty-five subjects were assigned to receive sham therapy, short-wave diathermy heat therapy, or single-leg interval exercise training, localized to the quadriceps muscles of the right leg. All interventions took place 3 times per week. Muscle biopsies were performed at baseline, and after 3 and 6 weeks of intervention. Mitochondrial respiratory capacity was assessed on permeabilized muscle fibers via high-resolution respirometry. RESULTS: The primary finding of this work was that heat therapy and exercise training significantly improved mitochondrial respiratory capacity by 24.8 ± 6.2% and 27.9 ± 8.7%, respectively (p < 0.05). Fatty acid oxidation and citrate synthase activity were also increased following exercise training by 29.5 ± 6.8% and 19.0 ± 7.4%, respectively (p < 0.05). However, contrary to our hypothesis, heat therapy did not increase fatty acid oxidation or citrate synthase activity. CONCLUSION: Six weeks of muscle-localized heat therapy significantly improves mitochondrial respiratory capacity, comparable to exercise training. However, unlike exercise, heat does not improve fatty acid oxidation capacity.